Analysis of The Influence of Social Commerce Tiktok Shop on Purchase Intention - Umarni, Yunita; Abdul Aziz, Muh; Alhidayatullah, Alhidayatullah (International Journal of Social Science, Education, Communication and Economics, 2024)
The digital era has driven the development of social media platforms as a means of transaction known as social commerce. TikTok Shop is one of the platforms that is increasingly in demand by consumers for online shopping, so it is important to understand the factors that influence social commerce and purchase intention. This study aims to analyze the effect of accessibility and promotion on social commerce, as well as its impact on purchase intention on TikTok Shop users in Sukabumi Regency. With a quantitative approach, this study involved 140 respondents who had made at least three purchases. The data analysis technique used Structural Equation Modeling (SEM) with the AMOS program. The results of the study indicate that social commerce has a significant effect on accessibility (P Value = 0.000; CR = 4.443) and promotion (P Value = 0.034; CR = 2.116). In addition, purchase intention also has a significant effect on social commerce (P Value = 0.000; CR = 4.513) and accessibility (P Value = 0.049; CR = 1.972). However, purchase intention does not have a significant effect on promotion (P Value = 0.304; CR = 1.027). This study strengthens previous findings that show the importance of social commerce in increasing accessibility and promotion, as well as the relevance of purchase intention in influencing social commerce and accessibility. The implications of this study can help business actors to design more effective marketing strategies, especially through social media platforms such as TikTok Shop.